Development and evaluation of virtual reality cases for clinical reasoning training in primary care: A Pilot Study at Hue University of Medicine and Pharmacy - Nguyen, Minh Tam; Huynh, Van Minh; Martin, Valcke; Le, Van Chi; Nguyen, Duc Hoang; Che, Thi Len Len; Duong, Quang Tuan; Nguyen, Hoang Bach; Ho, Dac Truong An; Le, Ho Thi Quynh Anh; Nguyen, Vu Quoc Bao; Nguyen, Vu Quoc Huy (Tạp chí Y Dược Huế, 2025)
Background: Integrating virtual reality (VR) into medical education can revolutionize teaching and learning clinical reasoning, yet it remains relatively limited in Vietnam. This study represents the first effort to develop and evaluate VR-based clinical cases for clinical reasoning training at Hue University of Medicine and Pharmacy. Methods: This quasi-experimental study uses a pretest‐posttest design with 298 fifth-year medical students. VR scenarios were designed to simulate clinical reasoning skills, including ordering laboratory tests, providing diagnoses, and making clinical decisions. A structured questionnaire assessed students’ readiness for VR-integrated learning, while clinical reasoning skills were evaluated using a four-station OSCE format and a VR-based examination. Results: A VR system and cases for clinical reasoning training were developed. The majority of students showed high readiness for VR-integrated learning. The paired sample T-test revealed significant improvements in clinical reasoning skills, with a mean OSCE score increase of 4.85 (p < 0.001). Significant gains were observed in students’ abilities to suggest medication regimens, provide diagnoses, and order diagnostic tests (p < 0.001) but not in health behavior management planning. Conclusions: Our study highlights the value of VR in enhancing clinical reasoning skills, supporting the evidence for VR-based education in healthcare. Improving VR training, incorporating an integrated curriculum design, and fostering multidisciplinary collaboration in creating VR cases are strongly recommended to optimize learning outcomes